Investigation of the Surface Tension Coefficient of the Depressant Additive and Components of Oil - Gurbanov, G.R.; Adygezalova, M.B.; Pashayeva, S.M. (Herald of Azerbaijan Engineering Academy, 2021)
For the first time in laboratory conditions, the coefficient of surface tension of the depressant additive "Difron-4201" and polar-molecular asphaltene-resinous components of highly paraffinic model oil were determined. During the experiment, a solution of depressant additive and asphaltene-resinous components in toluene was used. The concentration of the solution was increased to a constant value of the surface tension coefficient was established, and water was used as the standard liquid. The ring detachment method (du Noüy) was used to determine the tension coefficient of the surface of the depressant additive and asphaltene-resinous heterocomponents, and the measurement process was carried out on a tensiometer with a relative error of ± 1%. The results of the experiments showed that the surface tension coefficient increases with an increase in the concentration of the additive, asphaltene-resinous components in the solution. Analysis of the values obtained during the measurements showed that the surface tension coefficient of the asphaltene components of the highly paraffinic model oil is higher than the surface tension coefficient of the depressant additive Difron-4201, and the surface tension coefficient of the resin components is close to the value obtained in the additive. This result gives reason to believe that it is the resin components that affect the effectiveness of the depressant additive.